Detection of cyclonic and anti-cyclonic eddy in relation to potential Skipjack Tuna fishing ground in Makassar Strait. (March 2019) - Hidayat, R; Zainuddin, M
Abstract: Makassar Strait is one of best fishing ground in Indonesia. The distribution of skipjack tuna can be detected with oceanography factor. The purpose of this study was to determine the characteristics of eddies which has a relationship to chlorophyll-a in determining the skipjack tuna habitat. The study used geostrophic current data from AVISO which consisted of U (zonal component) and V (meridian component), chlorophyll-a data with spatial resolution of 4 km together with skipjack tuna catch. This research took place in May – July 2017. We used the satellite data of geostrophic current to identify the eddy fields. The results showed eddy intensity in Makassar Strait took place approximately 6-7 days until new eddy appeared. Two types of eddy (cyclonic and anti-cyclonic) were found in Makassar Strait waters. The cyclonic eddy location was appeared in Barru and Palu waters while the anti-cyclonic eddy was detected in the south of Makassar Strait. In addition, the distribution of chlorophyll-a in cyclonic eddy was higher than in anti-cyclonic eddy fields. We found that the occurrence of cyclonic and anti-cyclonic eddies are an important step toward defining skipjack tuna habitat which in turn, play an essential role for fishing operation and management.